2001
DOI: 10.1097/00004647-200108000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Caveolin-1 in Estrogen-Mediated Regulation of Endothelial Nitric Oxide Synthase Function in Cerebral Arterioles In vivo

Abstract: The marked impairment in cerebrovascular endothelial nitric oxide synthase (eNOS) function that develops after ovariectomy may relate to the observation that the abundance of cerebral vascular eNOS and its endogenous inhibitor, caveolin-1, vary in opposite directions with chronic changes in estrogen status. The authors endeavored, therefore, to establish a link between these correlative findings by independently manipulating, in ovariectomized female rats, eNOS and caveolin-1 expression, while monitoring agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 22 publications
2
52
2
Order By: Relevance
“…It is well known that estrogen exerts its cardioprotective effects rapidly or chronically via nitric oxide, 24,25 and that estrogen regulates nitric oxide synthase function and nitric oxide production through caveolin-1, which is the principle coat protein of caveolae. 26 However, the role of nitric oxide in raloxifene-induced cardioprotection seems to be minimal, because an inhibitor of nitric oxide synthase, L-NAME, did not show significant inhibitory effects of raloxifene. In previous studies, either raloxifene or idoxifene was shown to cause vasorelaxation, mainly in a nitric oxide-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that estrogen exerts its cardioprotective effects rapidly or chronically via nitric oxide, 24,25 and that estrogen regulates nitric oxide synthase function and nitric oxide production through caveolin-1, which is the principle coat protein of caveolae. 26 However, the role of nitric oxide in raloxifene-induced cardioprotection seems to be minimal, because an inhibitor of nitric oxide synthase, L-NAME, did not show significant inhibitory effects of raloxifene. In previous studies, either raloxifene or idoxifene was shown to cause vasorelaxation, mainly in a nitric oxide-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Age-matched female Sprague-Dawley rats (300 -350 g) were used (supplied by Charles River; Wilmington, MA). Pial arteriolar reactivities were evaluated using a closed cranial window and intravital microscopy system (39). The windows were placed on the day preceding study using a procedure described in a previous paper from our laboratory (39).…”
Section: Methodsmentioning
confidence: 99%
“…Pial arteriolar reactivities were evaluated using a closed cranial window and intravital microscopy system (39). The windows were placed on the day preceding study using a procedure described in a previous paper from our laboratory (39). The rats were anesthetized with halothane, intubated, paralyzed with a short-acting muscle relaxant (vecuronium), and mechanically ventilated with a 0.8% halothane-70% N 2O-30% O2 gas mixture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…64 In agreement with this finding, long-term estrogen depletion after ovariectomy is accompanied by an upregulation of (cerebral) endothelial caveolin-1 expression in vivo. 65,66 Ion Channel Regulation Several ion channels have been shown to be associated with caveolae (Table). These channels play a very important role in the regulation of endothelial barrier functioning, because they are involved in the regulation of endothelial cell permeability, transcytosis, angiogenesis, and the response to shear stress.…”
Section: Caveolae Caveolin-1 and Atherosclerosismentioning
confidence: 99%